2011
DOI: 10.1002/cphc.201001040
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene⋅⋅⋅Furan Trimer Formation at 0.37 K as a Model for Ultracold Aggregation of Non‐ and Weakly Polar Molecules

Abstract: We have studied the aggregation process of (C(2)H(2))⋅⋅⋅furan trimers at ultracold temperatures (0.37 K) in helium nanodroplets. Computational sampling of the potential energy surface using the multiple-minima-hypersurface (MMH) approach yielded seven possible minimum structures, optimized at the MP2 level of theory with the cc-pVTZ and 6-311++G(d,p) basis sets. Experimentally, we could assign five transitions in the IR spectrum of acetylene-furan aggregates in the acetylene C-H(asym) stretch region between 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…the acetylene-furan trimer. 33 Therefore, we suggest that structures which correspond to a global minimum on the potential energy surface are formed preferentially, since a rotational realignment subsequent to cooling is feasible.…”
Section: Glycine-h 2 Omentioning
confidence: 88%
“…the acetylene-furan trimer. 33 Therefore, we suggest that structures which correspond to a global minimum on the potential energy surface are formed preferentially, since a rotational realignment subsequent to cooling is feasible.…”
Section: Glycine-h 2 Omentioning
confidence: 88%
“…43 In these cases, the intact gas-phase molecules were picked-up by the droplets, and the equilibrium conformer distribution at the vapor temperature was largely preserved upon cooling to 0.4 K. 44,45 Moreover, as molecular cluster systems condense within He droplets, metastable structures are often kinetically trapped behind small isomerization barriers (greater than about 100 cm −1 ), 39,40,[46][47][48] although there are notable exceptions. 49,50 For these systems, the sequential pick-up process results in cold monomers that condense and produce relatively small amounts of intermolecular vibrational kinetic energy, which can be effectively dissipated prior to cluster rearrangement.…”
Section: Bx 2 a Allyl Peroxy Radical Spectrummentioning
confidence: 99%
“…We are left to conclude either that zero-point/nonadiabatic effects render the interconversion of N-bound isomers barrierless or that, upon complexation in the vicinity of the N-bound potential well, the helium droplet is not capable of quenching the kinetic energy gain prior to its rearrangement over (or through) the ∼40 cm –1 barrier. This is not without precedent; previous work on (HF) n clusters and acetylene/furan clusters (for example) showed that barriers of similar magnitudes could be overcome during the aggregation process within the helium droplet. Future computations of the O–HCN potential surfaces, including spin–orbit coupling and nonadiabatic effects, , may be capable of providing further insight into this issue.…”
Section: Resultsmentioning
confidence: 97%